Soil health and environment issues in alternative methods of rice-wheat production systems - Singh, Geeta (Indian Farming, 2015)
Green manuring in rice followed by zero tillage in wheat seems to be a promising option for sustained and economic yield. There is growing awareness that agriculture should not only be high yielding, but also sustainable. Farmers concerned about the environmental sustainability of their crop production systems combined with ever-increasing production costs have begun to adopt and adapt improved management practices.